Arylesterase activity of paraoxonase 1 and intensity of oxidative processes in the blood of dialysis patients - Korol, L.; Stepanova, N.; Vasylchenko, V. (Ukrainian Journal of Nephrology and Dialysis, 2019)
This study aimed to investigate the arylesterase activity of paraoxonase 1 (PON-1) in patients with end-stage renal disease (ESRD) and its relationship with oxidative stress markers. Methods. We conducted a one-time prospective observational study involving 58 ESRD patients. Among them, there were 20 hemodialyses (HD) patients and 38 patients treated with peritoneal dialysis (PD). The activity of PON-1 in serum was determined spectrophotometrically by the number of phenolic complexes formed using phenylacetate. Besides, spectrophotometrically the concentrations of malondialdehyde, serum concentrations of ceruloplasmin, thiol groups and total peroxidase activity (TPA) of erythrocyte were determined. The reference group consisted of 30 conditionally healthy individuals. Results. The arylesterase activity of the PON-1 in reference group was 6.57 kU/L versus 2.25 kU/L in HD patients and 4.26 kU/L in PD patients (p ˂ 0.0001). A direct correlation was found between arylesterase activity of PON-1 and ceruloplasmin concentration (p = 0.004), and TPA (p = 0.02) in HD patients. The activity of PON-1 in the serum of PD patients was associated with high-density lipoproteins (p ˂ 0.0001). Conclusions. We observed a decrease in the arylesterase activity of PON-1 in ESRD patients compared to the control group. The lowest activity of PON-1 is determined in HD patients. Moreover, the association of the PON-1 activity with a decrease in antioxidant blood markers was found. The enzyme activity in PD patients correlated with increased blood HDL. Further studies involving a larger dialysis cohort of patients are needed to determine the pathogenetic role of PON-1 activity in the development of cardiovascular events in ESRD patients.